Analisis Interior Kamar Rawat Inap Rumah Rehabilitasi MMHC Jakarta terhadap Warna Hangat: ANALYSIS OF THE INTERIOR OF THE INPATIENT ROOM OF THE MMHC JAKARTA REHABILITATION HOUSE ON WARM COLORS - Felice, Felice; Damayantie, Irma (Program Studi Desain Interior Unikom, 2024)
MMHC (Madani Mental Health Care) is a mental health rehabilitation house focusing on improving mental health. A mental rehabilitation house is a facility that provides special mental health services that require a comfortable environment, including the interior, to support the patient's psychology. One of the interior elements that has a psychological effect is color. The correct application of color in the interior can support the comfortable atmosphere you want to create in a room, especially in inpatient rooms. In a mental rehabilitation house, the inpatient room is the room that will be used most often by patients. So the colors used must be appropriate and can provide a calming and comfortable effect. This writing aims to examine the role of warm color as an important aspect of the interior by choosing the right colors in inpatient rooms in mental rehabilitation houses. The research method used was qualitative with a descriptive approach carried out by observation and interviews with psychiatrists and several MMHC rehabilitation house administrators. The results of the research state that warm colors are the best colors for use in inpatient rooms in mental rehabilitation houses. It is hoped that this writing will be useful for the world of developing interior design science in designing mental rehabilitation houses. Keywords: Interior Design, Inpatient Room, Warm Color, Mental Rehabilitation House